Co-authorship networks of scientific elite: case study of information science in Croatia - Pečarić, Đilda (Array, 2016)
Relatively small number of scientists receives large number of citations. Researches of most cited authors who form scientific elite are often. What is rare are researches of co-authorship of most cited authors. In this paper we research co-authorship networks of most cited authors in information science in Croatia. Overview of social characteristics of co-authorship networks or whether authors and co-authors belong to the university or research institute is given. Also, position of most cited authors in co-authorship networks is researched: a) order of co-authors and their position in the scientific elite according to time periods ; b) the institutional affiliation ; c) international collaboration. We try to use bibliometric methods for detecting, identifying and visualizing social, institutional and intellectual networks and impact of scientific elite